2015
DOI: 10.1007/s10753-015-0208-z
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Edema in the Lung and Kidney of Hemorrhagic Shock Rats Are Alleviated by Biliary Tract External Drainage via the Heme Oxygenase-1 Pathway

Abstract: The lung and kidney are two organs that are easily affected by hemorrhagic shock (HS). We investigated roles of biliary tract external drainage (BTED) in inflammation and edema of the lung and kidney in HS and its relationship with the heme oxygenase-1 (HO-1) pathway. Rat models of HS were induced by drawing blood from the femoral artery until a mean arterial pressure (MAP) of 40 ± 5 mmHg was achieved. A MAP of 40 ± 5 mmHg was maintained for 60 min. Thirty-six Sprague-Dawley rats were randomized to the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In the occurrence of ALI, the edema fluid is serious exudation, mainly containing water and plasma protein. In previous studies, HO-1 activation decreased the water content of lung tissues in ALI, suggesting an inhibitory role of HO-1 in edema development (19). The present study revealed that hemin preserved the ability of alveolar epithelia to initiate the vectorial fluid transport after LPS exposure.…”
Section: Discussionmentioning
confidence: 71%
“…In the occurrence of ALI, the edema fluid is serious exudation, mainly containing water and plasma protein. In previous studies, HO-1 activation decreased the water content of lung tissues in ALI, suggesting an inhibitory role of HO-1 in edema development (19). The present study revealed that hemin preserved the ability of alveolar epithelia to initiate the vectorial fluid transport after LPS exposure.…”
Section: Discussionmentioning
confidence: 71%
“…The right lower lobe of the lung was subsequently isolated, placed in liquid nitrogen and stored at -80˚C until use in western blot analysis. The presence of pulmonary edema was evaluated by measuring the ratio of dry/wet lung weight as described previously (13).…”
Section: Methodsmentioning
confidence: 99%
“…Edema, endothelial and epithelial damage followed by a release of cytokines and chemokines, activation, recruitment and extravasation of leukocytes are the characteristics features of ventilator-induced lung injury (VILI) [ 96 ]. There has been extensive evidence to support a protective role of HO-1 activation in VILI by decreased pro-inflammatory cytokine expression including TNF-α, IL-8, decreased neutrophil, etc., and increased expression of anti-inflammatory cytokines like IL-10 [ 97 , 98 ].…”
Section: Effect Of Ho-1 Activation On Inflammation and Coagulationmentioning
confidence: 99%